2012
DOI: 10.1590/s0100-67622012000600020
|View full text |Cite
|
Sign up to set email alerts
|

Aplicación de boro en eucalipto: comparación de fuentes

Abstract: La deficiencia de boro (B) en sistemas forestales ha sido reportada en diferentes especies de pino y eucalipto, verificándose importantes mejoras en la producción y/o calidad de madera, con el agregado de este nutriente. La baja retranslocación del B dentro de la planta hace necesario un aporte constante para satisfacer las demandas del cultivo. Al ser un nutriente muy poco retenido por el suelo está sujeto a pérdidas por lixiviación. El uso de fertilizantes solubles brinda una solución a corto plazo, muy depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…These results are in agreement with those obtained by Ferrando and Zamalvide (2012), who reported in a study performed in Uruguay that sources of B with different solubilities applied at planting did not significantly influence the foliar concentrations of the element, i.e., both the medium and high solubility sources provided good availability of B to the eucalyptus trees because the leaf B concentrations were within the range considered adequate for the species studied. ns -not significant by the F test, at 5% probability.…”
Section: Resultssupporting
confidence: 92%
“…These results are in agreement with those obtained by Ferrando and Zamalvide (2012), who reported in a study performed in Uruguay that sources of B with different solubilities applied at planting did not significantly influence the foliar concentrations of the element, i.e., both the medium and high solubility sources provided good availability of B to the eucalyptus trees because the leaf B concentrations were within the range considered adequate for the species studied. ns -not significant by the F test, at 5% probability.…”
Section: Resultssupporting
confidence: 92%
“…Em se tratando do manejo sem irrigação, Mattiello et al (2009) relatam que mesmo com baixo teor deste nutriente ou com o déficit hídrico, o boro ainda é assimilado pelo eucalipto por meio do fluxo difusivo. Esse aumento de concentração de boro pode ser atribuído à resposta da cultura do eucalipto na emissão de raízes mais profundas diante de ambientes com menor disponibilidade hídrica (FERRANDO;ZAMALVIDE, 2012), propiciando a maior probabilidade do encontro de B no solo e sua absorção.…”
Section: Resultsunclassified
“…When in forest sites in Uruguay, Ferrando & Zamalvide (2012) evaluated the effect from B sources with different solubilities (ulexite and sodium borate) at the 4 g plant -1 dose of B, and concluded that both sources provide foliar concentrations of B within the range considered suitable for cultivation. In this study, there was no difference between sources, since both provided adequate concentrations of foliar B for eucalyptus, according to the range considered adequate by Gonçalves (2011), 30-60 mg kg -1 of B.…”
Section: ( )mentioning
confidence: 99%